ORAL STORYTELLING AND FOLKLORES AS PRECURSORS TO WRITTEN LITERATURE IN THE REGION - Sevaraxon Jabaraliyeva Nozimjon kizi, Nargiza Toirova Isaqovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
Modernistic manifestations in Uzbek literature can be seen as a response to the changing social, cultural, and political landscape of Uzbekistan during the 20th century. The Modernist movement in Uzbek literature was influenced by broader global literary trends and sought to break away from traditional forms and themes.